Zapotin mitigates breast cancer progression by targeting PKCε mediated glycolytic pathway regulation - Khushbukhat Khan; Maryam Anwar; Yasmin Badshah; Naeem Mahmood Ashraf; Arslan Hamid; Janeen H. Trembley; Maria Shabbir; Tayyaba Afsar; Fohad Mabood Husain; Dilawar Khan; Suhail Razak (BMC Cancer)
Abstract Background The breast cancer recurrence and chemoresistance has increased over the years. A novel PKC, PKCε, may promote chemoresistance by causing hypoxia and cancer metabolic rewiring. A natural flavonoid, Zapotin, in colon cancer cells may modulate PKCε expression. Therefore, this study aimed to explore Zapotin impact on PKCε expression and the metabolic profile of breast cancer cells. Methods Pharmacophore analysis of Zapotin was performed and molecular dynamics (MD) simulations were employed to study PKCε and Zapotin interaction stability. The effect of Zapotin treatment on PKCε expression and various aspects of cancer cell viability and metabolism was studied in MCF-7 and MDA-MB-231 breast cancer cell lines using real-time PCR, growth and death assays, and Gas Chromatography-Mass Spectrometry. Results In silico analyses revealed good solubility and absorption of Zapotin with lower toxicity. Zapotin showed cancer cell-specific cytotoxicity (P < 0.0001). It’s treatment also reduced breast cancer cell viability, colony formation, and migratory potential by targeting PKCε and associated HIF-1ɑ and VEGF signaling (P < 0.01). Zapotin also impacted PKCε-mediated metabolic signaling by targeting glycolytic pathways. Conclusion This study demonstrated the role of PKCε mediated HIF-1ɑ, VEGF, and glycolytic pathways in promoting breast carcinogenicity and demonstrated Zapotin as a potential treatment option for different types of breast tumors.